2004
DOI: 10.1083/jcb.200408165
|View full text |Cite
|
Sign up to set email alerts
|

Recycling endosomes can serve as intermediates during transport from the Golgi to the plasma membrane of MDCK cells

Abstract: The AP-1B clathrin adaptor complex is responsible for the polarized transport of many basolateral membrane proteins in epithelial cells. Localization of AP-1B to recycling endosomes (REs) along with other components (exocyst subunits and Rab8) involved in AP-1B–dependent transport suggested that RE might be an intermediate between the Golgi and the plasma membrane. Although the involvement of endosomes in the secretory pathway has long been suspected, we now present direct evidence using four independent metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
434
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(463 citation statements)
references
References 48 publications
27
434
2
Order By: Relevance
“…More importantly, using the exo70-1 mutant in the EXO70 RNAi knockdown cells, we were able to specifically examine the functional significance of Exo70-PI(4,5)P 2 interaction in VSV-G exocytosis. The exocyst has been found in various cellular compartments, including Golgi and recycling endosomes, in addition to the PM Fö lsch et al, 2003;Ang et al, 2004;Langevin et al, 2005). Here we found that the Exo70-PI(4,5)P 2 interaction is not involved in the early stages of VSV-G trafficking through the endoplasmic reticulum and Golgi.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…More importantly, using the exo70-1 mutant in the EXO70 RNAi knockdown cells, we were able to specifically examine the functional significance of Exo70-PI(4,5)P 2 interaction in VSV-G exocytosis. The exocyst has been found in various cellular compartments, including Golgi and recycling endosomes, in addition to the PM Fö lsch et al, 2003;Ang et al, 2004;Langevin et al, 2005). Here we found that the Exo70-PI(4,5)P 2 interaction is not involved in the early stages of VSV-G trafficking through the endoplasmic reticulum and Golgi.…”
Section: Discussionmentioning
confidence: 59%
“…This localization pattern contrasts that of the membrane fusion machine, the t-SNAREs, which are evenly distributed along both the mother and daughter cell membrane (Brennwald et al, 1994). In mammalian cells, the exocyst components were found in the cytosol, recycling endosomes and trans-Golgi network Fö lsch et al, 2003;Ang et al, 2004;Langevin et al, 2005). However, they are recruited to the PM during a number of cellular processes.…”
mentioning
confidence: 85%
“…The observation of an alternative pathway for APP exit from the TGN also raises the possibility that some fraction of APP is always routed via the endosomal/lysosomal route (also see Ang et al, 2004 and related studies) and that it is the abundance and relative affinities of different binding partners that determines the percentage of APP that traffics between the different alternative paths, which in turn could have an important impact on processing and A␤ generation. For example, LR11/SorLa is a lipoprotein receptor with links to Alzheimer's disease (Andersen et al, 2005;Offe et al, 2006;Rogaeva et al, 2007) that binds directly to APP in their lumenal domains (Andersen et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Vamp8 is a component of secretory granules in secretory exocrine tissues (Wang et al, 2004;Weng et al, 2007), but is localized to a subset of endosomes in cell types that lack secretory granules (Wong et al, 1998;Antonin et al, 2000;Steegmaier et al, 2000). Both Sdmg1 and Vamp8 appear to have a function in cells lacking secretory granules (Antonin et al, 2000;Best et al, 2008), possibly related to the role of some endosomes in the secretory pathway in polarized epithelial cells (Ang et al, 2004;Lock and Stow, 2005). However, it is not clear at present what the biochemical function of Sdmg1 might be in the endosomal membrane, or whether Sdmg1 performs a similar biochemical function in secretory granule membranes.…”
Section: Discussionmentioning
confidence: 99%